2019
DOI: 10.3390/jmse7060168
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Electric Propulsion Systems in Ships Using an Active Front-End Rectifier

Abstract: In the case of the electric propulsion system on the vessel, Diode Front End (DFE) rectifiers have been applied for large-sized ships and Active Front End (AFE) rectifiers have been utilized for small and medium-sized ships as a part of the system. In this paper, we design a large electric propulsion ship system using AFE rectifier with the proposed phase angle detector and verify the feasibility of the system by simulation. The phase angle derived from the proposed phase angle detection method is applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Among the many types of alternative fuels and alternative propulsion systems for ships, hybrid propulsion and increasingly pure electric propulsion are frequently mentioned in the literature [19][20][21][22][23]. Both of these types of propulsion systems are inhomogeneous in every respect; while they have in common the fact that they are technological innovations, in ship propulsion and that they are at an early stage of development, they are represented very narrowly in shipping practice.…”
Section: Hybrid and Electric Ship Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the many types of alternative fuels and alternative propulsion systems for ships, hybrid propulsion and increasingly pure electric propulsion are frequently mentioned in the literature [19][20][21][22][23]. Both of these types of propulsion systems are inhomogeneous in every respect; while they have in common the fact that they are technological innovations, in ship propulsion and that they are at an early stage of development, they are represented very narrowly in shipping practice.…”
Section: Hybrid and Electric Ship Propulsionmentioning
confidence: 99%
“…Both of these types of propulsion systems are inhomogeneous in every respect; while they have in common the fact that they are technological innovations, in ship propulsion and that they are at an early stage of development, they are represented very narrowly in shipping practice. All existing cases of using pure electric propulsion can be met in linear shipping where a very short distance is the subject of the service, i.e., an estimated for 20-40 Nm [19,21,24]. Hybrid propulsion is the combination of two or more alternative sources of energy used for both the propulsion of the ship and the operation of onboard equipment.…”
Section: Hybrid and Electric Ship Propulsionmentioning
confidence: 99%
“…The common rectifier schemes used in the DC third rail system are 6-pulse [17], [18], 12-pulse [5], [16], [19], 18-pulse rectifiers [20] and 24-pulse rectifiers [6], [21]. These rectifiers generate the characteristic harmonics in the order of (ℎ = 𝑛𝑘 ± 1) where n is the number of pulses and k is an integer number.…”
Section: Introductionmentioning
confidence: 99%
“…This research confirmed the excellence of fuel-cells being used as ship power systems. In addition, Jeon et al [4]…”
mentioning
confidence: 99%
“…This research confirmed the excellence of fuel-cells being used as ship power systems. In addition, Jeon et al [4] introduced an excellent Active-Front-End (AFE) rectifier applicable for a large electric propulsion ship system. Through a series of simulation, they confirmed the technical maturity of the AFE rectifier as well as the feasibility of the system.…”
mentioning
confidence: 99%